Novel Photonic Structures and Materials - Fawzy, Samar (AUC Knowledge Fountain, 2022)
Plasmonic materials provide the ability to confine light in metallic structures in the nanometre scale, enabling their use in a wide range of applications, including metamaterials, energy conversion, biomedical applications, and transformation optics. Conventional plasmonic materials such as Silver and Gold suffer from two problems: very large negative real permittivity (𝜀1), preventing their integration with low-permittivity dielectrics, and large losses associated with conduction electrons such as: electron-electron scattering, electron-phonon scattering or scattering by crystal defects. Therefore, the search for alternative structures and materials that overcome these obstacles is indeed an essential task. Metamaterials, three dimensional (3D) periodic subwavelength metallic/dielectric structures, resonantly couple to the electromagnetic waves, leading to unprecedented or unusual properties and features that cannot be achieved using conventional materials. Due to the usually associated high losses and strong dispersion and spectral dependence associated with the resonant responses, in addition to the difficulty of fabricating 3D metamaterials, practical applications were relatively limited. On the other hand, metasurface is a category of metamaterials that inherent all the properties of metamaterials while providing a solution to the limitations of such structures. Phase-gradient metasurfaces (PGM) exploit phase accumulation along the transverse directions to manipulate the incident wave front. Dielectric metasurfaces provide a more efficient option compared to their plasmonic metallic counterparts, owing to their low Ohmic losses, and minimal back scattering. Most regular shaped dielectric metasurfaces such as spheres, cubes, cylinders, and rods use the lowest order Mie-type resonances namely magnetic and electric dipoles (MD & ED respectively) to engineer the desired phase gradient. Moreover, the usually high refractive index can lead to strongly confined fields with minimal dissipation. Therefore, in the first part of the dissertation, the first route is considered to overcome the iii problematic lossy metals via nanostructuring. An all-dielectric Silicon-based novel perturbed structure, Bipodal Cylinder (BPC), is presented. The complex geometry of BPCs provides several degrees of structural freedom. This structure is proposed as the building unit cell for a high-performance beam steering PGM. In the second part of the dissertation, the second route is explored to tackle the previously discussed issues of metals via material doping. Transparent conducting oxides (TCOs) were shown to provide a route of tailoring the plasma frequency, provide means to all-semiconductor plasmonics, while maintaining low losses and being CMOS compatible. Therefore, we investigate the effect of different potential defects in Zinc Oxide (ZnO) using first-principles calculations on the low-loss plasmonic performance of defective/doped ZnO as a TCO. The SPP characteristics of interstitial Hydrogen (H) and substitutional Aluminium (Al)-doped ZnO were also investigated. Both H-ZnO and Al-ZnO showed almost similar behaviour, backing the argument that H doping can be used as an alternative to the problematic Al. Moreover, insights on the reasons for the low-loss plasmonic nature of H doped ZnO are provided and discussed. Finally, the potential use of H-ZnO in metamaterials and metasurfaces is introduced through numerically showing that Fano-resonance can be excited in near-IR using a simple symmetric cylinder with an air hole made of hydrogen-doped ZnO placed on pure ZnO substrate, revealing its potential use in numerous applications. Finally, the use of Bismuth as a high-index dopant in ZnO was explored to produce a high-index birefringent material. With the desired properties of Bismuth, we study the effects of using it as a dopant in three metal oxides using density functional theory (DFT). We then focus on ZnO due to the promising optical properties achieved, including giant birefringence, increased in-plane index and negative real permittivity. To understand the changes in the structure caused by the incorporation of Bi, Bader charge analysis is performed. Insights regarding varying the doping concentration, inclusion of Oxygen vacancies and co-doping with Hydrogen and Aluminium are discussed.